PEMANFAATAN GUA-GUA ALAM DI KABUPATEN MOROWALI UTARA SEBAGAI BUKTI AKTIVITAS MANUSIA MASA LALU - nfn Sriwigati (Balai Arkeologi Provinsi Sulawesi Utara, 2018)
Human life in the past, especially in the late Pleistocene and early Holocene are very dependent on the availability of natural resources around them. One of adaptation to an environment that does is use the cave as a shelter. The location was chosen with consideration of the cave near the water source, easy to get the food needed and is safe from the threat of wild animals. Natural caves scattered Morowali district is used as a shelter and burial with the remains of stone-tool artifacts flakes, blades and waste product; kitchen midden and animal bones: skull, bones and human teeth; rock painting in the form of hand stencils.